The Palestinian mammalian fauna acquired by the zoological gardens in the Gaza Strip - ABDEL FATTAH N. ABD RABOU (Nusantara Bioscience, 2011)
Abstract. Abd Rabou AFN. 2011. The Palestinian mammalian fauna acquired by the zoological gardens in the Gaza Strip. Nusantara Bioscience 3: 82-91. The Gaza Strip, which is an arid strip of the Palestinian land along the southeastern Mediterranean, harbors a considerable number of mammalian fauna due to its eco-geo-strategic position. Prior to 2006, the establishment of zoological gardens in the Gaza Strip was a sort of imagination due to Israeli constraints. These constraints were nurtured by the total Israeli destruction and demolition of the Rafah and Gaza private zoological gardens in 2004 and 2009 respectively, using heavy tanks and bulldozers. The establishment of many zoological gardens following the Israeli evacuation from the Gaza Strip in late 2005 encouraged wildlife trading. Hence, the current study comes to document the Palestinian mammalian faunistic species acquired by the zoological gardens in the Gaza Strip through frequent visits to Gaza zoological gardens and meetings with local people, wildlife hunters, and zoo owners. A total number of 17 Palestinian mammalian faunistic species belonging to 12 families and 5 orders was encountered in the zoological gardens throughout the study period. The encountered species represent a good mix of the families and sizes of mammals generally found in other parts of Palestine. Order Carnivora represents 52.94% of the caged mammals, while the orders Rodentia, Lagomorpha, Artiodactyla and Insectivora represent 47.06%. The study documented the first sight of the Greater Egyptian Gerbil Gerbillus pyramidis in the Gaza Strip. Local hunting, tunnel trade and delivery were the lonely sources of the mammals encountered in the zoological gardens. The economic deprivation under the current Israeli blockade and the poor implementation of environmental laws and legislation concerning wildlife protection have made wildlife trading as a common practice. Finally, The author recommends to improving the management process of Gaza zoological gardens under the care of the governmental authorities and the cooperation of the different parties in the Gaza Strip to enhance public ecological awareness to protect and conserve wildlife; especially mammals.